Isolation and quantification of phytosterols in fresh and processed shoots of an edible bamboo Bambusa bambos (L.) Voss using GC-MS - Natasha Saini; Chongtham Nirmala Madho Singh Bisht
Bamboo shoot is considered a palatable delicacy in Southeast Asia and Northeastern India and is traditionally consumed in fresh, boiled, soaked and fermented forms. Despite having high nutritious value, bamboo shoot is a minimally explored food resource, particularly for bioactive compounds. The present study was conducted to explore the phytosterols in shoots of Bambusa bambos (L.) Voss and how they were affected by processing techniques such as boiling, soaking and fermentation. The total phytosterol content in fresh shoots was 198.69 mg/100g in terms of dry weight. Lipid extraction, followed by isolation of sterol fraction and examination through GC-MS, revealed the presence of three major free phytosterols with the highest content of gb(B-sitosterol followed by campesterol and stigmasterol. All the processing techniques lead to the enhancement of phytosterol content for each of the free sterols and, in totality, where fermentation was most effective, bringing about a better constitution of phytosterols, which can provide many health functions. Thus, bamboo shoots could be used as a healthy food commodity in fresh as well as processed form, and its extracted sterols could be fortified in various supplements, drugs and health care productss